2022
DOI: 10.1371/journal.pone.0271385
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination status, favipiravir, and micronutrient supplementation roles in post-COVID symptoms: A longitudinal study

Abstract: Introduction Post-COVID symptoms are the new concern in the COVID-19 pandemic, where recovered patients experience residual symptoms affecting their quality of life. Therefore, it is imperative to evaluate the role of complete vaccination, prescribed medication, and micronutrients during COVID episodes in the occurrence of post-COVID symptoms. Method A longitudinal evaluation of Indonesia’s recovered COVID-19 patients was performed using the data collected from July 2021 and extracted in mid-February 2022. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The previous survey conducted during alpha, beta, and Delta waves showed a similar prevalence of post-COVID-19 symptoms [8]. Fatigue remains the most reported post-COVID-19 symptom in this study and is similar to the reported prevalence in a meta-analysis [23].…”
Section: Omicron Infection Was Milder Than Deltasupporting
confidence: 86%
See 2 more Smart Citations
“…The previous survey conducted during alpha, beta, and Delta waves showed a similar prevalence of post-COVID-19 symptoms [8]. Fatigue remains the most reported post-COVID-19 symptom in this study and is similar to the reported prevalence in a meta-analysis [23].…”
Section: Omicron Infection Was Milder Than Deltasupporting
confidence: 86%
“…The researcher selected chronic cough as the primary outcome due to the nature of the SARS-COV2 infection. The initial study demonstrated that the Indonesian population's incidence of chronic cough within 30 days after COVID-19 was 17.3% [8]. With a 95% confidence level, a 5% margin of error, and 10% of non-responsive participants, the estimated sample size was 242.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Second, another surprising finding was the short-lasting nature of the headache. This could be related with the high prevalence of prior influenza infection (31%), the prior occurrence of headache in the context of other infections (61%), and the proportion of patients who had been previously vaccinated (21%), as it has been observed in patients with SARS-CoV-2 (22,23). This points toward the immune response as a likely generator of the headache, suggesting that treatments should minimize the negative consequences of the immune activation, without preventing its physiologic function (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, although late-onset or persistent complications of COVID-19 have been reported, including active shortness of breath, cough, asthma, and other respiratory complications, no cases of late-onset pneumonia were seen, unlike our study [ 11 ]. Another study reported that vaccination could reduce residual symptoms following COVID-19 in the general population [ 12 ]. However, these persistent or residual symptoms in the general population are different and less severe than the late-onset and exacerbated symptoms of the KTRs in our study, which required medical attention and subsequent hospitalization.…”
Section: Discussionmentioning
confidence: 99%